Electrochemical redox processes involving soluble cerium species. (1st July 2016) - Arenas, L.F.; Ponce de León, C.; Walsh, F.C.
Graphical abstract: Highlights: The relevance of cerium in laboratory and industrial electrochemistry is considered. The history of fundamental electrochemical studies and applications is considered. The chemistry, redox thermodynamics and electrode kinetics of cerium are summarised. The uses of cerium ions in synthesis, energy storage, analysis and environmental treatment are illustrated. Research needs and development perspectives are discussed. Abstract: Anodic oxidation of cerous ions and cathodic reduction of ceric ions, in aqueous acidic solutions, play an important role in electrochemical processes at laboratory and industrial scale. Ceric ions, which have been used for oxidation of organic wastes and off-gases in environmental treatment, are a well-established oxidant for indirect organic synthesis and specialised cleaning processes, including oxide film removal from tanks and process pipework in nuclear decontamination. They also provide a classical reagent for chemical analysis in the laboratory. The reversible oxidation of cerous ions is an important reaction in the positive compartment of various redox flow batteries during charge and discharge cycling. A knowledge of the thermodynamics and kinetics of the redox reaction is critical to an understanding of the role of cerium redox species in these applications. Suitable choices of electrode material (metal or ceramic; coated or uncoated), geometry/structure (2-or 3-dimensional) and electrolyte flow conditions (hence an acceptable mass transport rate) are critical to achieving effective electrocatalysis, a high performance and a long lifetime. This review considers the electrochemistry of soluble cerium species and their diverse uses in electrochemical technology, especially for redox flow batteries and mediated electrochemical oxidation.